PERLINDUNGAN HUKUM TERHADAP PEMAIN SEPAK BOLA DI INDONESIA ATAS HAK POKOKNYA - Sihasale, Giovanni Gianini; Setyadji, Sri; Hufron (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. Revealing the legal protection of football players as workers in the football